Submucosal Giant Lipoma of the Colon as an Unusual Cause of Partial Intestinal Occlusion: Report on Seven Consecutive Cases - Kafadar, Mehmet Tolga; Dalbaşı, Erkan; Oğuz, Abdullah; Aday, Ulaş (Turkish Journal of Gastroenterology, 2021)
Background: Colonic lipomas begin to be symptomatic when they reach a certain size, although the presentation can vary. In this study, we aimed to evaluate our experiences with the management of patients who presented with symptomatic giant colonic lipomas. Methods: The data of 7 patients with single colonic lipoma were retrospectively reviewed. The following data were evaluated: age, gender, clinical and diagnostic findings, American Society of Anesthesiologists (ASA) score, operative findings, postoperative complications, mortality, hospital stay duration, and hospital readmission. The diagnosis of colonic lipoma was established by computed tomography (CT). Results: In this study, 4 (57.1%) of 7 patients with colonic lipoma were female, and 3 (42.9%) were male. The mean age was 56.7 years (range, 45-69). The main symptoms were abdominal pain (100%), and constipation (71.4%). The findings of intestinal occlusion detected on CT confirmed the diagnosis in all patients. Colon lipoma was located in the ascending colon in 2 patients, in the hepatic flexure in 2 patients, in the transverse colon in 2 patients, and in the cecum in 1 patient. The surgical procedure was uneventful in all patients. Four (57.1%) patients underwent laparoscopic colonic resection, while in the remaining 3 (42.9%) patients, a laparotomy was performed. The mean operating time was 185.7 min (150-210). Length of stay was 7.1 days (6-10), with no mortality. The mean diameter of the lesions was 7.4 cm (6-9). At a 6-month follow-up, all patients were asymptomatic with no signs of recurrence. Conclusion: Although colon lipomas are rare, they are of great importance because they can be symptomatic and can be confused with colon malignancies in the differential diagnosis. Being able to make a definitive preoperative diagnosis will change the surgical strategy. A minimally invasive surgical approach should be employed to resect symptomatic colonic lipomas with an experienced surgical team in eligible patients whenever possible.